Prophylaxis for the International Traveller - MacPherson, D. W. (1985)
Travellers should know as much as possible about the quality of food and drink in the areas of travel, and be prepared with safety measures if necessary. Routine immunization should be up to date; cholera and yellow fever vaccinations are required for travel to certain areas. Such prophylaxis should be sought, ideally, several months before departure. Resurgences of malaria are occurring in areas where the disease had previously been controlled, making prophylaxis essential for travel to endemic areas. Other mild disorders may be treated with medication appropriate to the type of travel and area. Patients may appreciate cautionary advice about behavior, to lessen the likelihood of physical or social harm.